Complete Mitochondrial Genome of Niphon spinosus (Perciformes: Niphonidae): Genome Characterization and Phylogenetic Analysis - Maheshkumar Prakash Patil; Jong-Oh Kim; Seung Hyun Yoo; Jiyoung Shin; Ji-Young Yang; Kyunghoi Kim; Gun-Do Kim (Biomolecules)
The species Niphon spinosus (Cuvier, 1829) is the only representative of the family Niphonidae and the genus Niphon, and its taxonomic history is complicated; it is still unclear in a phylogenetic sense. In this study, we report the complete mitochondrial genome of N. spinosus (OP391482), which was determined to be 16,503 bp long with biased A + T contents (53.8%) using next-generation technology. The typical set of 13 protein-coding genes (PCGs), 2 rRNA genes, 22 tRNA genes, and one control region (D-loop) are included in the mitochondrial genome. The H-strand encoded 28 genes (14 tRNA, 2 rRNA, and 12 PCGs), and D-loop, whereas the L-strand encoded the remaining 9 genes (8 tRNA and ND6). Its nucleotide composition, gene arrangement, codon usage patterns, and tRNA secondary structures are identical with other members of the Percoidei suborder. Furthermore, we reconstructed phylogenetic trees based on the 13 PCGs. The resulting phylogenetic trees showed N. spinosus placing as a separate lineage within the family Niphonidae, its close relationship to Trachinus draco (Trachinidae), and the clustering of major subfamilies like Luciopercinae and Percinae of the Percoidei suborder. These findings will contribute to future studies on the evolutionary history, population genetics, molecular taxonomy, and phylogeny of N. spinosus and related species.